Rationale and Practical Techniques for Mouse Models of Early Vein Graft Adaptations - Yu, Peng (2010)
Mouse models serve as relatively new yet powerful research tools to study intimal hyperplasia and wall remodeling of vein bypass graft failure. Several model variations have been reported in the past decade. However, the approach demands thoughtful preparation, selected sophisticated equipment, microsurgical technical expertise, advanced tissue processing and data acquisition. This review compares several described models, and aims (building on our personal experiences) to practically aid the investigators who want to utilize mouse models of vein graft failure.